Assessment of damage of Endodontic Instruments with Naked Eye and Optical Instruments - Antonela Šošić; Ivan Šalinović; Valentina Brzović Rajić; Ana Ivanišević Malčić; Silvana Jukić Krmek; Ivana Miletić (University of Zagreb. School of Dental Medicine, 2021)
Objectives: To determine the accuracy of visual damage evaluation of rotating and reciprocal endodontic instruments with the naked eye and optical devices. Material and methods: Four examiners were involved, divided into two age groups: I. 20-30 years, n = 2, II. 40-50 years, n = 2. They visually assessed the existence of damage to rotating or reciprocal endodontic instruments by their naked eye and with two types of optical aids. A total of 239 instruments from different manufacturers were evaluated by each examiner. Before damage estimation, each examiner calibrated the eye on a new instrument. Sensitivity of the detection method was calculated as by the naked eye. When an instrument was detected as damaged by the naked eye, the damage assessment was stopped and the instrument was considered to be damaged by the other two methods, as well. Results: Damage was found in 178 instruments. Sensitivity of the naked eye was calculated to be 49.7%, for the loupe 66.2% and for the operating microscope 76.5%. The three methods of damage assessment had significant differences (p < 0.05) in sensitivity. Conclusion: It was concluded that there is a significant difference between age groups in estimating instrument damage. Also, it was noted that the damage assessment with the naked eye and optical aids were different. Finally, in terms of ease of damage recognition, significant differences between the types of engine-driven endodontic instruments were found. However, no type of instrument was more prone to damage than any other type of instrument.